194k views
4 votes
What is the 4th term for D(n)=3(-2)n-1

User Kreya
by
6.4k points

1 Answer

0 votes

Answer:

47

Explanation:

The general term of the sequence "D" is given by the formula:


D_n=3(-2)^(n)-1

Where

n represents the nth term.

Here, we need to find the 4th term, so n = 4.

If we plug in 4 into n, we can find the value of the 4th term.

Lets do this:


D_n=3(-2)^(n)-1\\D_4=3(-2)^(4)-1\\D_4=3(16)-1\\D_4=48-1\\D_4=47

Hence,

The 4th term of this sequence is 47

User Kenm
by
6.1k points